PELATIHAN PENCATATAN KEUANGAN BAGI UMKM di SEKOLAH KEWIRAUSAHAAN BINA AMANAH CORDOVA, TANGGERANG - Rina Hartanti; Ratna Darasih; Koramen Haulian Sirait (ASOSIASI IDEBAHASA KEPRI, 2022)
Abstract Abstract :The importance of education in improving the quality of life of a nation and state is well recognized by the Bina Amanah Cordova Entrepreneurship School as an Entrepreneurial Human Resource educational institution that provides free education to high school graduates who have economic constraints in continuing their education to a higher level of education and allow a definitive answers regarding the existing economic constraints. The School of Entrepreneurship Bina Amanah Cordova is in dire need of Lecture who can provide knowledge and skills in accounting through financial recording training for Micro, Small and Medium Enterprises (UMKM). Therefore, the Faculty of Economics and Business - Trisakti University in order to help meet the needs of these teaching staff, in collaboration with the Bina Amanah Cordova Entrepreneurship School carry out Community Service (PKM) by providing practical training on recording MSME financial transactions in accordance with SAK-ETAP Accounting standards. , begins with an explanation of the understanding and accounting process starting from recording financial transactions in journals to the posting process to the general ledger and financial statements, practicing accounting questions, and discussing financial recording problems that Cordova students still face. The results after the PKM implementation were in line with expectations, where participants were very enthusiastic about asking about SAK-ETAP accounting and answering the accounting exercises given.